BUILDING ELEMENTARY SCHOOL STUDENT CHARACTERS THROUGH THE STRENGTHENING OF THE PANCASILA VALUES IN THE DISRUPTION ERA - Apiek Gandamana; Peny Husna Handayani (Universitas Negeri Medan, 2020)
Abstract: The emergence of the disruption era marked by the development of advances in digital technology is something that cannot be avoided. This technological advancement has a positive impact that can be enjoyed by humans, but also has a negative impact. The negative impact can threaten the character of students such as the entry of new ideas that can erode the noble values of Pancasila. Pancasila is a way of life for all Indonesian people in various fields of their lives. Elementary school students as the next generation are the main target in strengthening Pancasila values, so that students who are characterized by Pancasila can be realized. Strengthening Pancasila values must be done early by habituation and exemplary. Strengthening Pancasila values and the role of parents, teachers, government and the use of the educational environment both in families, schools and communities is very important in shaping the mindset and attitude so that elementary school students are able to make Pancasila values as a reference in facing the current era of disruption. Keywords: character, disruption, Pancasila valuesAbstrak: Munculnya era disrupsi yang ditandai dengan perkembangan kemajuan teknologi digital menjadi hal yang tidak dapat dihindari. Kemajuan teknologi ini memiliki dampak positif yang bisa dinikmati manusia, namun juga berdampak negatif. Dampak negatif tersebut dapat mengancam karakter siswa seperti masuknya ide-ide baru yang dapat menggerus nilai-nilai luhur Pancasila. Pancasila merupakan pedoman hidup bagi seluruh rakyat Indonesia dalam berbagai bidang kehidupan. Siswa SD sebagai generasi penerus merupakan sasaran utama dalam penguatan nilai-nilai Pancasila, sehingga siswa yang bercirikan Pancasila dapat terwujud. Penguatan nilai-nilai Pancasila harus dilakukan sejak dini dengan pembiasaan dan keteladanan. Penguatan nilai-nilai Pancasila dan peran orang tua, guru, pemerintah serta pemanfaatan lingkungan pendidikan baik dalam keluarga, sekolah maupun masyarakat sangat penting dalam membentuk pola pikir dan sikap agar siswa sekolah dasar mampu menjadikan nilai-nilai Pancasila sebagai acuan dalam menghadapi era gangguan saat ini. Kata kunci: karakter, gangguan, nilai-nilai Pancasila